PENERAPAN ASAS RESTORATIVE JUSTICE DALAM TINDAK PIDANA PENCEMARAN NAMA BAIK DI WILAYAH KEJAKSAAN NEGERI BALIGE - Hutagaol, Daniel Pandapotan; Megawaty, Wenny (Legal Standing : Jurnal Ilmu Hukum, 2023)
Defamation involves accusing a person of some act in order to gain public knowledge. The problem in the case of criminal defamation suspect Hotman Hutadjulu with Maruli Tua victims is still the family scope. The process of justice that takes considerable time and is less able to revive the relationship between the suspect and the victim, and thus has a restorative justice for the completion of the libel crime crime, in accordance with the Republic of Indonesia Prosecutor’s No. 15 of 2020. This research is aims to explain the implementation of the restorative justice principle in criminal defamation in District Attorney’s Balige District of Toba North Sumatera. The research approach method used was juridical normative, with analytic descriptive research specification. The research used a secondary data. Data were analyzed using qualitative methods of analysis. The results of this research application of the restorative justice principle in criminal defamation has been done effectively and in accordance with legislation. The burden the state Attorney Balige faces are having difficulty connecting the suspect with the victim to mediate and information unknown.